Psychometric Properties of the Children’s Automatic Thoughts Scale (CATS) in 10-16-year-old children in Golestan Province - Mohsen Jalali; Elnaz Pourahmadi (روانشناسی بالینی و شخصیت)
Introduction: Negative automatic thoughts play a crucial role in childhood psychiatric disorders. It is essential to develop and validate an effective tool for assessing automatic thoughts in children. The aim of the present study is to investigate the psychometric properties of the Children’s Automatic Thoughts Scale (CATS) in children aged 10 to 16 years in Golestan Province.Method: This study employed a survey methodology. The research sample consisted of 453 children aged 10 to 16 in Golestan Province, selected through a multistage cluster random sampling method. Participants were evaluated using the CATS, RCAMS, CDI, and YSR assessments. Finally, the data were analyzed using the Pearson correlation coefficient, Cronbach's alpha, and factor analysis.Results: The results of the exploratory factor analysis of the CATS items revealed a four-factor structure. Cronbach's alpha values ranged from 0.70 to 0.86, and the test-retest reliability coefficients, measured over a 14-day interval, ranged from 0.68 to 0.83. Convergent validity was established by calculating the significant correlations between the total CATS score and its four subscales, as well as with the subscales of the YSR, RCAMS, and CDI (p < 0.01).Discussion and conclusion: The Persian version of CATS appears to have satisfactory psychometric properties and can be utilized in educational, clinical, and research settings.